Cytotoxicity of an unprecedented brominated oleanolide and a new furoceramide from the Cameroonian spice, Echinops giganteus. Issue 22 (16th November 2016) - Sandjo, Louis P.; Kuete, Victor; Siwe, Xavier N.; Poumale, Herve M. P.; Efferth, Thomas
Abstract: A preliminary study on Echinops giganteus (Asteraceae) showed that the methanolic extract has interesting cytotoxicities against a panel of cancer cell lines. From this extract, a lignan, a flavonoid and a polyacetylenic thiophene identified were three times less cytotoxic than the extract. In the search of the metabolites responsible for the bioactivity, a new harvested E. giganteus was subjected to a phytochemical study using chromatographic methods. In the course of the work, two new compounds: a brominated oleanolide (1 ) and a tetrahydrofurano-ceramide (2 ) were obtained along with β-amyrin acetate (3 ), 2-(penta-1, 3-diynyl)-5-(4-hydroxybut-1-ynyl)-thiophene (4 ), 2-(penta-1, 3-diynyl)-5-(3, 4-dihydroxybut-1-ynyl)-thiophene (5 ) and 4-hydroxy-2, 6-di-(3′, 4′-dimethoxyphenyl)-3, 7-dioxabicyclo-(3.3.0)octane (6 ). Their structures were determined on the basis of NMR spectroscopy and mass spectrometry data in conjunction with those reported in the literature. The cytotoxicity of1, 2 and5 was evaluated by employing resazurin assay against a panel of cancer cell lines with IC50 values in range 6.12 ± 0.46–46.96 ± 3.61 μM. Abstract :